Innovation of interlocking IBS wall panels / Ain Zarifahazyan Muhamad Shukri and Mohd Rofdzi Abdullah - Muhamad Shukri, Ain Zarifahazyan; Abdullah, Mohd Rofdzi (2023)
Industrialised Building System (IBS) wall panels are a promising solution in the construction industry for improving construction efficiency, reducing costs, and enhancing sustainability. These prefabricated panels offer numerous benefits, including faster construction timelines, minimised labour requirements, improved quality control, and elevated potential for energy savings. However, several challenges exist including design limitations, transportation logistics, integration with other building systems, skilled labour requirements, initial investment costs, and regulatory considerations.